Human papillomavirus and oral and oropharyngeal carcinoma: the essentials. (7th October 2018) - Yakin, M; Seo, B.; Hussaini, H; Rich, A; Hunter, K
Abstract: There is a global increase in the prevalence of human papillomavirus (HPV)‐driven oropharyngeal squamous cell carcinoma (OPSCC) in Australia and New Zealand. Risk factors for HPV‐positive OPSCC are male gender, white race, age older than 40 but younger than 59 years old, having multiple lifetime sex partners, having oro‐genital and oro‐anal sex. High‐risk HPV subtypes play a major role in the pathogenesis of OPSCC, however, they play a much lesser role in oral squamous cell carcinoma (OSCC). Among the laboratory tests used to detect oncogenic HPV infection, polymerase chain reaction is a sensitive method but does not reflect the role of HPV in oncogenesis. While widely used, p16 immunohistochemistry is both a sensitive and a specific surrogate marker for oncogenic HPV infection in OPSCC, but not in OSCC. However, it is a useful prognostic marker in OPSCC. The current gold standard to accurately detect oncogenic HPV infection is E6/E7 mRNA in situ hybridization. Because both HPV‐positive and p16‐positive OPSCC have better short‐term prognoses there is current debate and trials on treatment de‐escalation in HPV‐positive OPSCC. Dental practitioners can play an important role in early diagnosis of HPV‐positive OPSCC.